2021
DOI: 10.3390/ijms222011266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gut Bacterial Communities of Fall Armyworm (Spodoptera frugiperda) Reared on Different Host Plants

Abstract: Spodoptera frugiperda is a highly polyphagous and invasive agricultural pest that can harm more than 300 plants and cause huge economic losses to crops. Symbiotic bacteria play an important role in the host biology and ecology of herbivores, and have a wide range of effects on host growth and adaptation. In this study, high-throughput sequencing technology was used to investigate the effects of different hosts (corn, wild oat, oilseed rape, pepper, and artificial diet) on gut microbial community structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 76 publications
(152 reference statements)
5
43
0
Order By: Relevance
“…In this study, the midgut bacterial and fungal communities of S. frugiperda larvae fed on two cruciferous vegetables, B. campestris and B. oleracea , and an artificial diet, were analyzed. There was a significant difference in the diversity and abundance of the midgut bacterial and fungal communities when S. frugiperda larvae fed on different plants, which was similar to the results reported in many previous findings in Lepidoptera 4 , 23 , 37 . This is the first time we investigated the effects of cruciferous vegetables on the microorganisms in S. frugiperda larvae, which enriched the diversity of the midgut microbial community of S. frugiperda and provided a preliminary understanding of the role of midgut microbes in S. frugiperda larvae feeding on cruciferous vegetables.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the midgut bacterial and fungal communities of S. frugiperda larvae fed on two cruciferous vegetables, B. campestris and B. oleracea , and an artificial diet, were analyzed. There was a significant difference in the diversity and abundance of the midgut bacterial and fungal communities when S. frugiperda larvae fed on different plants, which was similar to the results reported in many previous findings in Lepidoptera 4 , 23 , 37 . This is the first time we investigated the effects of cruciferous vegetables on the microorganisms in S. frugiperda larvae, which enriched the diversity of the midgut microbial community of S. frugiperda and provided a preliminary understanding of the role of midgut microbes in S. frugiperda larvae feeding on cruciferous vegetables.…”
Section: Discussionsupporting
confidence: 89%
“…The influences of different genotypes of maize ( Zea mays ), including B73, Tx601, and Mp708, on S. frugiperda larval midgut community structure and composition were also explored 22 . Significant differences in gut microbial community structure and diversity were exhibited when the larvae fed on different hosts 23 , 24 . These studies could contribute to the research of the host adaptation of S. frugiperda and the development of efficient and environmentally friendly control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum bacterial population in the gut of the field caught population might be due to the availability of more nutrients from the natural host plants while the availability of nutrients might be lower in the artificially reared population. Dongbiao et al [27] suggested that the high abundance of Firmicutes in the gut of Spodoptera frugiperda larvae is due to the better absorption of different nutrients. Studies showed that Enterococcaceae and Lactobacilli were stable across the different growth stages of S. littoralis and H. armigera [28].…”
Section: Discussionmentioning
confidence: 99%
“…Plant seeds were purchased from an agricultural company (Shouhe Co., Ltd., China). Plants were grown through the three to four true-leaf stage before being employed in the studies ( Lv et al, 2021 ). They were housed in cages at a temperature of 25 ± 3°C, with a relative humidity of 70 ± 10 percent and a photoperiod of 16 h light and 8 h dark.…”
Section: Methodsmentioning
confidence: 99%